Prosumer Behavior Related to Running a Household in Rural Areas of the Masovian Voivodeship in Poland - Paulina Trębska; Agnieszka Biernat-Jarka; Marcin Wysokiński; Arkadiusz Gromada; Magdalena Golonko (Energies, 2021)
The subject of research is a phenomenon of prosumption, i.e., the intertwining of consumption and production processes, until the differences between them are blurred. When consumers produce goods and services for their use, they become prosumers. The article aimed to assess consumer behavior in terms of various forms of prosumer activity on the market of household-related services. The types of prosumer activity of rural households and their size were determined during the analyses. The article uses primary sources from a survey conducted among residents of rural areas of the Masovian Voivodeship in Poland in 2017. Statistical, descriptive, and comparative methods were used. The research shows that consumers are very active in the field of prosumption, rationally running their households. The study used principal component analysis (PCA) and selected descriptive statistics. The research results showed that the services performed can be grouped into three categories, i.e., the index of basic living self-sufficiency of households, the index of renovation and repair self-sufficiency, and the index of professional self-sufficiency of farms. Consumers usually prepare meals at home and clean, iron, and wash clothes, thus reducing the costs of running a household. It is also popular to carry out repairs oneself or to carry out repairs of equipment at home.